Analisis Hukum Terkait Penerapan Special Purpose Acquisition Company (SPAC) di Indonesia - Ryoko Sugama, Ni Made (UNES Law Review, 2023)
Future developments in the business world and the opportunity to carry out an Initial Public Offering (IPO) process using a company with a Special Purpose Acquisition Company (SPAC) model are increasingly in demand and developing in the International and Asian Capital Markets. SPAC is known as a shell company that has no previous operational history, business activities or assets that generate business income during the Initial Public Offering or IPO process. A SPAC is a shell company formed specifically to acquire one or more operating companies through a business combination. SPAC has the goal of conducting an IPO by using IPO proceeds along with an equity rollover to fund a business combination. However, as regulated in provision III.1.1. Indonesian Stock Exchange Regulation Number I-A concerning the Listing of Shares and Equity Securities Other than Shares Issued by Listed Companies limits that legal entities that can list their shares on the Stock Exchange are legal entities in the form of Limited Liability Companies. Thus, a legal basis is needed for SPAC to be implemented.